IMPROVING SKILL WRITING AND LEARNING MOTIVATION USING DEDUCTIVE APPROACH - Yuyun Wahyudin; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2018)
This research is to know the difference of learning effectiveness using deductive approach and ordinary approach used by a teacher in this case study based on curriculum 2013. In improving the performance of writing skill of poem. This research method is a quasi-experiment research. Data collection was done with pre-test and post-test. Achievement of poem writing skills is measured using objective description and questionnaire/ attitude scale. The results showed that (1) there was a significant difference between learning using the deductive approach and the usual approach in improving the performance of poem writing skills, shown in the Independent Samples Tes test for Equality of Means, with sig score. (2 tailed) of 0.026 (2) that the motivation to learn greatly affect the learning achievement of writing poem, this is shown in the output of Independent Samples T-test column for Equality of Means, with sig score. (2 tailed) of 0.153 (3) there is a significant correlation between learning motivation and achievement with a correlation coefficient of 0.736 (strong).